Factors affecting the graduation rate in the University of the Philippines College of Dentistry - Buenaventura, Criszel F.
Introduction. Doctor of Dental Medicine is a 6 year course. For the past 2005-2010 batches, 75 to 100% were delayed from graduation and thus took dentistry for more than 6 years. This is a high percentage compared to the less than 23% for those who graduated on time on the said batches. The attrition rate increases through time except with batch 2007 that broke the increase yet still after the said batch, the attrition rate still increases.